PROCESS MODEL OF INFORMATION TECHNOLOGIES OUTSOURCING ORGANIZATION FOR STATE COMPREHENSIVE COMPLEXES - M. Lisitsyn; N. Lyubimova (Вестник университета)
The problem of organization of information techologies (IT) outsourcing for gen-eral education complexes in Moscow is considered. As a result of research into public pro-curement of IT outsourcing services for general education complexes a low level of technical support of the IT infrastructure by IT outsourcing companies and consequently frequent ear-ly termination of the concluded contracts of general education complexes with IT companies has been revealed. The method of a two-stage open tender for public procurement of IT out-sourcing services was developed and criteria (qualication requirements) of the choice of an IT company for public procurement that should improve the quality of services provided and reduce the percentage of prematurely terminated contracts in the future, -has been suggested.